Promosi Kesehatan Terkait Telehealth di Dunia dan Indonesia - Riskha Dora Candra Dewi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The ability of people and communities to take charge of their own health and well-being is greatly enhanced by health promotion. Sick persons do not have to be physically present at the health service facility in order to receive services through telemedicine or telehealth. The purpose of this study is to examine the global and Indonesian significance of health promotion related to telehealth. A literature review approach is used in this study. thorough search from 2017 to 2024 throughout electronic databases, such as PubMed, Science Direct, and Google Scholar. The findings of the study demonstrate that telehealth has enormous potential to revolutionize the provision of healthcare services around the world by providing chances to improve patient participation, expand access, and enhance health service outcomes. But in order to fully utilize telehealth, it's necessary to remove technological, cultural, and legal obstacle to implementation.